Opportunities, Challenges and Ethical Considerations as Insider-Researcher for a Community-Based Research in Redressing Livelihood Sustainability Issues - Emerson Abraham Jackson (Management of Sustainable Development. The Journal of "Lucian Blaga" University of Sibiu, 2018)
The thought about taking an ethical view-point to this research has emanated from the researcher's journey in preparing for a baseline survey of residents in Goderich using the Community-Based Research Participation (CBRP) approach to investigating concerns pertaining to sustainable livelihood needs. In as much as the overarching focus of the research is aimed at meaningful contribution to the body of knowledge, it was worth the effort in journeying through this phronetic / ethical exploration, which is not so common in research engagements carried out in developing countries like Sierra Leone. The role of the researcher as an insider was thoroughly explored, with the view of openness raised as the preferred option as a way of eliciting unbiased outcomes from participants and also, removing power domination, most often witnessed in researcher-participants relation with most research undertakings. – – L'idée de donner un point de vue éthique à cette recherche découle du parcours de la chercheuse dans la préparation d'une enquête de base sur les résidents de Goderich, qui utilise la méthode de la participation à la recherche basée sur la communauté (PRC) pour enquêter sur les préoccupations relatives aux besoins en moyens de subsistance durables. Dans la mesure où l'objectif principal de la recherche visait à apporter une contribution significative au corpus de connaissances, il valait la peine de tenter de parcourir cette exploration phronétique / éthique, qui n'est pas si courante dans les activités de recherche menées dans des pays en développement comme Sierra Leone. Le rôle du chercheur en tant qu'initié a été étudié de manière approfondie, la transparence étant perçue comme l'option privilégiée pour obtenir des résultats impartiaux des participants et également pour éliminer la domination du pouvoir, ce qui est le plus souvent observé dans la relation chercheur-participants avec la plupart des travaux de recherche.
Keywords: Q01; 330; Livelihood Sustainability; Sierra Leone; Insider-researcher; Ethics